Comparative transcriptome profiling of the fertile and sterile flower buds of a dominant genic male sterile line in sesame (Sesamum indicum L.). Issue 1 (December 2016) - Liu, Hongyan; Tan, Mingpu; Yu, Haijuan; Li, Liang; Zhou, Fang; Yang, Minmin; Zhou, Ting; Zhao, Yingzhong
Abstract Background Sesame (Sesamum indicum L.) is a globally important oilseed crop with highly-valued oil. Strong hybrid vigor is frequently observed within this crop, which can be exploited by the means of genic male sterility (GMS). We have previously developed a dominant GMS (DGMS) line W1098A that has great potential for the breeding of F1 hybrids. Although it has been genetically and anatomically characterized, the underlying molecular mechanism for male sterility remains unclear and therefore limits the full utilization of such GMS line. In this study, RNA-seq based transcriptome profiling was carried out in two near-isogenic DGMS lines (W1098A and its fertile counterpart, W1098B) to identify differentially expressed genes (DEGs) related to male sterility. Results A total of 1, 502 significant DEGs were detected, among which 751 were up-regulated and 751 were down-regulated in sterile flower buds. A number of DEGs were implicated in both ethylene and JA synthesis & signaling pathway; the expression of which were either up- or down-regulated in the sterile buds, respectively. Moreover, the majority of NAC and WRKY transcription factors implicated from the DEGs were up-regulated in sterile buds. By querying the Plant Male Reproduction Database, 49 sesame homologous genes were obtained; several of these encode transcription factors (bHLH089, MYB99, and AMS) that showed reduced expression in sterile buds, thus implying the possible role in specifying or determining tapetal fate and development. The predicted effect of allelic variants on the function of their corresponding DEGs highlighted several Insertions/Deletions (InDels), which might be responsible for the phenotype of sterility/fertility in DGMS lines. Conclusion The present comparative transcriptome study suggested that both hormone signaling pathway and transcription factors control the male sterility of DGMS in sesame. The results also revealed that several InDels located in DEGs prone to cause loss of function, which might contribute to male sterility. These findings provide valuable genomic resources for a deeper insight into the molecular mechanism underlying DGMS.